Teacher education in science and mathematics education: the current deviations of the profession in the structural crisis of capital (Research, Society and Development, 2020)
The training of teachers is an essential part for the realization of the objective of education, considering that the teacher is the agent responsible for the transmission of knowledge, it is necessary that the teacher has access to good training. Thus, in order to analyze the training of teachers for teaching chemistry, a bibliographic review was made to analyze the importance of adequate training in the light of Marxist thoughts. With an approach to the public school system, more specifically of students from the 1st grade of High School, in which the difficulty that these students bring with knowledge already acquired in previous grades is verified, this reflects in the difficulty of learning more specific content that has as prerequisite basic subjects that the students were not able to master at the Fundamental Level. It is possible to observe the lack of teacher training, so it is necessary to analyze how education is inserted in the capitalist system, what is the role, the role that education plays in this system in which we live. To this end, it relies on the arguments of several authors who share a common basis: equality between all, a society without distinction between classes, with everyone being treated in the same way, and with the same rights and duties.